2020
DOI: 10.1007/s11199-020-01136-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relation between Gender Typicality and Pressure to Conform to Gender Norms

Abstract: Previous research suggested that gender typicality and pressure to conform to gender norms were unrelated; however, this may have been due to how gender typicality was assessed (i.e., by only comparing the self to one's own gender collective). In the present study, we used a dual identity approach (comparing oneself to both gender collectives: to own-gender and other-gender individuals) to create typologies of gender typicality to examine how similarity to own and other gender collectives might differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 53 publications
2
34
0
2
Order By: Relevance
“…This might indicate a narrowing of the gender gap for communion as well. Younger generations of boys may feel more free to adopt communal attributes in their self-descriptions, despite stronger disapproval of gender role violations in boys (e.g., Kane, 2006;Sirin et al, 2004), as well as higher gender conformity pressure among boys than girls reported in previous studies (Egan & Perry, 2001;Nielson et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…This might indicate a narrowing of the gender gap for communion as well. Younger generations of boys may feel more free to adopt communal attributes in their self-descriptions, despite stronger disapproval of gender role violations in boys (e.g., Kane, 2006;Sirin et al, 2004), as well as higher gender conformity pressure among boys than girls reported in previous studies (Egan & Perry, 2001;Nielson et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…More precisely, social pressure notably from peers constrains some children, particularly boys, to avoid cross‐gender behaviours (Carver et al, 2003; Egan & Perry, 2001). Moreover, boys who feel more similar to other boys tend to pressure themselves to conform to gender norms (Nielson et al, 2020). These pressures may exert an important influence on boys' gender typicality, leaving less variance to be explained by other factors such as the mutual responsiveness of parent–child interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, children who feel similar to their own gender may, at the same time, feel quite similar to the other gender, while others do not. Thus, to reach a better comprehension of children's gender typicality, it is important to consider their perceived similarity to both genders (Andrews, Martin, & Gallagher, 2016; Martin et al, 2017; Nielson, Schroeder, Martin, & Cook, 2020; Pauletti, Menon, Cooper, Aults, & Perry, 2017), and indeed the authors of the original typicality scale (Egan & Perry, 2001) have also recently expanded their approach to use comparisons to both gender groups (Perry, Pauletti, & Cooper, 2019). Accordingly, here we define and measure gender typicality in terms of self‐perceived similarity to own‐ and other‐gender groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of societal norms about gender and of socialization experiences and regardless of their conformity, most adolescents feel a strong pressure to conform to gender-conforming characteristics (Galambos, 2013; Nielson et al, 2020). In fact, gender socialization often acts through peer rewards for gender-conforming behaviors and peer punishments for gender-nonconforming behaviors (Zosuls et al, 2016).…”
mentioning
confidence: 99%